Eosinophilic Esophagitis as One of the Manifestations of Gastrointestinal Food Allergy in Children - S.L. Niankovskyi; M.I. Horodylovska; V.A. Ivantsiv; O.I. Boiko (Zaslavsky O.Yu., 2015)
The article describes the features of clinical course and current approaches to the diagnosis and treatment of eosinophilic esophagitis in school-aged children. The study involved 63 children with suspected eosinophilic esophagitis, diagnosis was confirmed by endoscopic and morphological investigation only in 40 of them. Children with eosinophilic esophagitis were divided into two groups of 20 pupils, depending on the regimen. Children from the main group received elimination diet, levocetirizine and probiotic bacteria L.reuteri within one month, from the control one - just elimination diet and levocetirizine. It was found that the inclusion of probiotic L.reuteri into the combination therapy for eosinophilic esophagitis has a significant impact on the treatment outcomes in children that appears in better reduction of clinical symptoms and significant decrease in the number of eosinophils in the esophageal mucosa of children.